P382 Thinking outside the POX. (June 2019) - Reynolds, Claire; Cremin, Molly; Felsenstein, Susanna
Abstract : CASE REPORT: Background: Varicella zoster virus (VZV) causes chicken pox and shingles. Neurological manifestations occur in both illnesses. An exanthem is usually present except in the immunocompromised and elderly. Case: A 14 year old girl presented with headache, fever, vomiting and photophobia, though no meningism or altered consciousness. She was febrile, Glasgow Coma Scale was 15, she was fully orientated and conversing freely. Neurological exam revealed brisk deep tendon reflexes of all 4 limbs and ankle clonus bilaterally. The remainder of her examination was normal. There was no significant past medical history. Her vaccinations were up to date. Baseline bloods reported normal complete blood count, renal and hepatic profile, thyroid function tests and inflammatory markers. CT brain was normal. Lumbar puncture revealed a CSF protein of 1.4 g/L, glucose of 2.3 mmol/L, 356×10^9/L WBC, 99% of which lymphocytes. MRI brain and spine and EEG were normal. The patient underwent an extensive infectious diseases work up for viral, bacterial and fungal etiologies, autoimmune work up and flow cytometry of CSF in order to outrule a primary CNS malignancy. She received acyclovir and cefotaxime as empiric treatment for infectious meningoencephalitis. Given anamnestic potential for TB exposure, antimycobacterial combination therapy also was commenced. Subsequently, AFB stain and Mtb PCR on CSF were negative, as were bacterial and fungal PCRs and cultures. A chest XR, tuberculin skin test and IGRA all yielded a negative result. CSF virology identified varicella zoster virus positive PCR. The patient was treated for VZV meningoencephalitis most likely due to VZV reactivation following primary infection in early childhood. Flow cytometry of CSF leukocytes identified a high proportion (12%) of double negative T cells, with normal flow cytometry of peripheral blood. Her recovery was complicated by bilateral anterior uveitis two months after initial presentation which resolved on topical steroids. She completed a 21 day course of Aciclovir and recovered fully. Conclusion: We present a rare case of aseptic meningitis caused by VZV reactivation without exanthem in an immunocompetent patient. This case is instructive in posing a wide differential diagnosis including the possibility of viral meningoencephalitis, an evolving autoimmune process, postviral complications or treatment related adverse effects; and illustrates the need for a better understanding of the role of certain lymphocyte subsets in infectious and autoimmune disorders involving the central nervous system.